50 Years of Human Factors Psychology at Texas Tech University. (September 2017) - Klein, Martina I.; Halcomb, Charles; DeLucia, Patrica R.; Liddell, Greg; Chaparro, Barbara; Endsley, Mica
In 1966, the Human Factors Program Psychology of Texas Tech University (TTU) was inaugurated. The program has been accredited by HFES since 2002, when it was one of 14 accredited programs. The panel of former and current faculty (Drs. Halcomb, DeLucia, and Endsley) as well as successful alumni (Drs. Liddell and Chaparro) discusses the development of the program, how training at TTU's Human Factors Psychology Program prepared graduates for success, provides advice for current students, and also reflects on the challenges and the path for the future for the human factors profession and human factors training.